The Effect of Online Education on Children’s Socialization Processes During the Pandemic Period: A Communication- Based Research on First Grade Primary School Students - Ebru Özgen; Ayşe Müge Yazgan (Türkiye İletişim Araştırmaları Dergisi)
Isolated life emerged at a time when society was not ready during the 2020 pandemic (Covid-19) period. During this period, the structure of society, which has undergone significant social changes, has been transformed. It has been vital to adapt rapidly to the social isolation and distance from outside life within this new social structure. Digital technology is also a factor that changed the lives of students at school. The scope of this research includes 3rd-grade students in primary schools in three major cities of Türkiye: İstanbul, Ankara, and İzmir. This research aims to gather information about the social changes and social anxiety of the students during social isolation by analyzing the responses to scale questions used as a data collection tool, under the observation of parents and classroom teachers. The research design incorporates both quantitative and qualitative methodologies. The data collection tools used in this study are the Social- Emotional and Character Development Scale in the survey research, the Social Anxiety Scale for Children, and a personal information form prepared by the researchers. Results are augmented with semi-structured interviews. Data analysis is conducted using the SPSS 22.0 statistical software package. The results obtained indicate that students experience social anxiety as a result of isolation. It is observed that during the Covid-19 pandemic period, social isolation affected 1st-grade students in the 2020-2021 academic year. The findings suggest that as the level of social anxiety and social change increase, there is a decrease in social, emotional, and moral development.